Security, Privacy, and Applied Cryptography Engineering Third International Conference, SPACE 2013, Kharagpur, India, October 19-23, 2013, Proceedings - Gierlichs, Benedikt.; Gierlichs, Benedikt.; Guilley, Sylvain.; Guilley, Sylvain.; Mukhopadhyay, Debdeep.; Mukhopadhyay, Debdeep. (Security and Cryptology ;, 2013)
This book constitutes the refereed proceedings of the Third International Conference on Security, Privacy and Applied Cryptography Engineering held in Kharagpur, India, in October 2013. The 12 papers presented were carefully reviewed and selected from 39 submissions. The papers are organized in topical sections on implementations and protocols, side channel attacks and countermeasures, identity-based indentification schemes, and signatures.